PENERAPAN METODE BERCERITA DENGAN BONEKA TANGAN TERHADAP KEMAMPUAN BERBICARA ANAK TK B DI SEKOLAH NURUL FIKRI BANJARMASIN - Rika; Zulkarnaen, Muhammad; Yusuf, Muhammad; Nisa, Uswatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Cooperation Speaking ability is an essential aspect of early childhood language development that supports communication, social interaction, and the expression of ideas and feelings. Based on preliminary observations at TK Islam Terpadu Nurul Fikri Banjarmasin, the speaking ability of Group B children showed varying levels of development. Most children were able to communicate according to their developmental stage; however, some still experienced difficulties in expressing opinions, answering questions, constructing simple sentences, and retelling stories. This study aimed to describe the children's speaking ability before the implementation of the storytelling method using hand puppets and to describe its implementation in developing the speaking ability of Group B children. This study employed a descriptive qualitative approach involving 17 Group B children and one classroom teacher as the main informant. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings showed that the implementation of the storytelling method using hand puppets increased the children's enthusiasm for learning, encouraged them to answer questions and express their opinions more confidently, and improved their ability to retell stories using simple sentences appropriate to their developmental level. The teacher implemented the method by adjusting it to the learning themes, using varied voice intonation, and actively engaging the children throughout the learning activities. Therefore, the storytelling method using hand puppets created an enjoyable learning atmosphere and contributed to the development of the speaking ability of Group B children at TK Islam Terpadu Nurul Fikri Banjarmasin.